Impulsivity and risk taking in bipolar disorder and schizophrenia. - Reddy, L; Lee, J; Davis, M; Altshuler, L; Glahn, D; Miklowitz, D; Green, M (2014)
Impulsive risk taking contributes to deleterious outcomes among clinical populations. Indeed, pathological impulsivity and risk taking are common in patients with serious mental illness, and have severe clinical repercussions including novelty seeking, response disinhibition, aggression, and substance abuse. Thus, the current study seeks to examine self-reported impulsivity (Barratt Impulsivity Scale) and performance-based behavioral risk taking (Balloon Analogue Risk Task) in bipolar disorder and schizophrenia. Participants included 68 individuals with bipolar disorder, 38 with schizophrenia, and 36 healthy controls. Self-reported impulsivity was elevated in the bipolar group compared with schizophrenia patients and healthy controls, who did not differ from each other. On the risk-taking task, schizophrenia patients were significantly more risk averse than the bipolar patients and controls. Aside from the diagnostic group differences, there was a significant effect of antipsychotic (AP) medication within the bipolar group: bipolar patients taking AP medications were more risk averse than those not taking AP medications. This difference in risk taking because of AP medications was not explained by history of psychosis. Similarly, the differences in risk taking between schizophrenia and bipolar disorder were not fully explained by AP effects. Implications for clinical practice and future research are discussed.